TOR1AIP2 as a candidate gene for dystonia-hemichorea/hemiballism - Kafantari, Efthymia; Hernandez, Victoria J; Necpál, Ján; Leonidou, Marina; Baureder, Regina; Hedberg-Oldfors, Carola; Jech, Robert; Zech, Michael; Schwartz, Thomas U; Puschmann, Andreas (Parkinsonism & related disorders, 2025)
Dystonia is a movement disorder characterized by genetic and clinical heterogeneity. A recurring p.(Glu303del)-deletion in TOR1A is a well-established cause for DYT-TOR1A (DYT1), an autosomal dominant early-onset isolated dystonia. TOR1A encodes TorsinA, an AAA + ATPase located in the nuclear envelope. By whole exome analyses of a family with a novel dystonia-hemichorea-/hemiballism phenotype, we identified a TOR1AIP2 NM_001199260.2 c.1234A > G p.(Arg412Gly) variant. The variant is very rare in databases and was absent from whole exome data from >1000 dystonia patients. TOR1AIP2 encodes LULL1, a transmembrane protein that activates TorsinA, and correct interaction between TorsinA and LULL1 is essential for proper nuclear envelope architecture. The p.(Arg412Gly) variant disrupts the binding interface between TorsinA and LULL1 around p.Arg412; this same interface is also impaired in DYT1. Functional analyses via a co-purification assay revealed that interaction between TorsinA-LULL1Arg412Gly is weaker than the wild-type interaction, and that it resembles the situation in DYT1 (TorsinAΔE303-LULL1). A second family with milder dystonia, hemichorea, and stereotypic leg flexion during gait and a TOR1AIP2 p.(Gln338His) variant was identified. The clinical phenotype of both families shared proximal arm movements, and flutter in facial musculature. Expressivity of the movement disorder symptoms was variable. Several proteins in the nuclear envelope have been implicated in various forms of neurodevelopmental disorders with dystonia. Taken together, our findings suggest TOR1AIP2 as a new candidate gene implicated in a complex hereditary movement disorder with dystonia and hemichorea/hemiballism.
Keywords: dospělí; TOR1AIP2; dystonie; Female; Chorea; Pedigree; Adult; ženské pohlaví; dystonické poruchy; rodokmen; Dystonia; chorea; lidé; Dystonic Disorders; TorsinA; Molecular Chaperones; molekulární chaperony; Male; Nuclear envelope; dyskineze; DYT1; Hemichorea; lidé středního věku; Stereotypy; mužské pohlaví; Middle Aged; Hemiballism; Dyskinesias; Humans